Effectiveness of Spinal Stabilization Exercises on Movement Performance in Adults with Chronic Low Back Pain - Khalid Alkhathami; Yousef Alshehre; Kelli Brizzolara; Mark Weber; Sharon Wang-Price (International Journal of Sports Physical Therapy)
# Introduction